The Hydrodynamic Model Application for Future Coastal Zone Development in Remote Area - Surya Hermawan; David Bangguna; Edwin Mihardja; Jason Fernaldi; Jescey Edlin Prajogo (Civil Engineering Journal, 2023)
Indonesia is an archipelago country with a wealth of marine resources. However, local communities have not optimally utilized the use of natural resources, including those in the coastal zone of Central Sulawesi, Indonesia. This research goal is to identify the potential coastal areas for future development in the coastal zones, such as grouper floating net cage (FNC) culture, seaweed cultivation, and tourism areas. Thus, it is intended to develop the methodology of the hydrodynamic models for decision support systems (DSS) within the analysis hierarchy process. There are a total of 25 parameters criteria to calculate the potential future coastal zone development, including physics, water quality, and zoning properties. This DSS can serve as the foundation for instruction, knowledge, and application in developing rural coastal regions. Because of its breadth, this research endeavor is still ongoing. After calibration and verification, the initial study of the potential area of approximately 98,000 ha indicates that the model meets the accuracy requirement within the range of the root mean square error of approximately 0.184. Then, the outcomes of the hydrodynamic model simulation in DSS can be used as essential information for maritime development at this location. The outcomes demonstrate that the best areas for grouper FNC cultivation, seaweed cultivation, along with marine tourism are 6,163 ha, 91,000 ha, and 9,024 ha, respectively. It is expected that this research will contribute to sustainable future coastal zone development in the vicinity of Central Sulawesi, Indonesia.Â Doi: 10.28991/CEJ-2023-09-08-02 Full Text: PDF